2010
DOI: 10.1152/japplphysiol.00141.2010
|View full text |Cite
|
Sign up to set email alerts
|

Important role of muscle carnosine in rowing performance

Abstract: The role of the presence of carnosine (β-alanyl-L-histidine) in millimolar concentrations in human skeletal muscle is poorly understood. Chronic oral β-alanine supplementation is shown to elevate muscle carnosine content and improve anaerobic exercise performance during some laboratory tests, mainly in the untrained. It remains to be determined whether carnosine loading can improve single competition-like events in elite athletes. The aims of the present study were to investigate if performance is related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
160
5
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(190 citation statements)
references
References 36 publications
12
160
5
8
Order By: Relevance
“…Much of the positive effect was explained by significant improvements (p = 0.013) in exercise capacity, although BA did not significantly improve exercise performance (p = 0.204). However, it should be noted that few studies have addressed the effect of BA on sports-specific tasks, and the findings of those that have are conflicting (Derave et al 2007;Van Thienen et al 2009;Baguet et al 2010;Bellinger et al 2012;Saunders et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the positive effect was explained by significant improvements (p = 0.013) in exercise capacity, although BA did not significantly improve exercise performance (p = 0.204). However, it should be noted that few studies have addressed the effect of BA on sports-specific tasks, and the findings of those that have are conflicting (Derave et al 2007;Van Thienen et al 2009;Baguet et al 2010;Bellinger et al 2012;Saunders et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous research using trained participants [52,100,116,132]. The authors suggest that the wrestlers in the study may have been restricting their carbohydrate intake in order to make weight for an upcoming competition and every wrestler (in both groups)…”
Section: S)supporting
confidence: 91%
“…Stellingwerf et al [98] hypothesised that individuals with low baseline carnosine levels such as vegetarians, females or the elderly [58], might respond to a greater extent to β-alanine supplementation than those having higher resting concentrations. However, contrary to this hypothesis Baguet et al [100] found a positive correlation between high baseline levels and the increase in M-Carn in eight elite rowers. In addition, no relationship between baseline carnosine levels and increases in M-Carn was found in 21 young males [101].…”
Section: β-Alanine Supplementationmentioning
confidence: 76%
See 1 more Smart Citation
“…Although carnosine is not involved in the classic ATP-generating metabolic pathways, this suggests an important role of the dipeptide in the homeostasis of contracting muscle cells, especially during high rates of anaerobic energy delivery. Carnosine can offset acidosis by acting as a pH buffer, but improved contractile performance may also be obtained by enhanced excitation-contraction coupling and defence against reactive oxygen species [26][27][28][29][30][31]. Betaalanine is rapidly rising as a popular ergogenic nutritional increment for athletes worldwide, and the currently accessible scientific prose proposes that its practice is evidence-based.…”
Section: Carnosinementioning
confidence: 99%